Validação de material educativo para homens com cateter vesical de demora no domicílio - Medeiros, Adriane Pinto de (Universidade Federal de São Carlos, 2012)
This methodological study aimed to develop and validate educational material and illustrative writing for men with urinary indwelling catheters at home. We conducted a literature review on guidelines related to the theme proposed for the content of the material. Nineteen articles were included in the review, fourteen studies selected from PubMed, CINAHL and 2 in 3 in LILACS. It was used as theoretical framework health literacy and health education and as methodological framework, the model of content validation of diagnostic proposed by Fehring (1987) and the assessment of the Suitability assessment of educational materials. The educational material consists of a brief introduction entitled Catheter care at home, and 32 guidelines organized into 10 thematic categories: body care, urinary catheter care and the collection bag, emptying the collection bag, when I should use gloves, fixing probe, care about liquids and food, sexual activity, care in relation to return to activities, to whom was undergone prostate surgery, and warning signs. We carried out the content and appearance validation of the material with 30 experts and all guidelines were validated with the final score greater than or equal to 0.8. Most experts assessed positively the appearance of the material, with an average of 89.7% of positive responses on 16 items assessed. Despite the use of numerical scales for the validation of the content and yes and not for answers in the appearance validation, it was shown that in such a study, the availability of spaces for the experts to give an opinion has proved of great value for improving the quality of the material. The experts contributed with suggestions for improved presentation of the material and illustrations, suggestions for terms commonly used by customers and questions about the adequacy of guidance and illustrations given. The guidelines have been reorganized and obtained 27 guidelines divided into 10 thematic categories, as well as introductory content. The results can provide the base for nursing practice and allow to perform new studies in clinical validation in order to obtain evidence about the impact of using this kind of material in achieving positive outcomes with clients, as well the possibility of subsidizing the development of protocols and / or specific plans of care and thus possibly facilitate nursing activities and consequently improve the recovery and quality of life of the clients.
Keywords: Enfermagem; Cateterismo urinário; Educação e saúde; Autocuidado; Homem; Urinary catheterization; Health education; Nursing; Self care; CIENCIAS DA SAUDE::ENFERMAGEM